Culture and Organizational Climate: Nurses’ Insights Into Their Relationship With Physicians - Malloy, David Cruise (Nursing ethics, 2009)
Within any organization (e.g. a hospital or clinic) the perception of the way things operate may vary dramatically as a function of one’s location in the organizational hierarchy as well as one’s professional discipline. Interorganizational variability depends on organizational coherence, safety, and stability. In this four-nation (Canada, Ireland, Australia, and Korea) qualitative study of 42 nurses, we explored their perception of how ethical decisions are made, the nurses’ hospital role, and the extent to which their voices were heard. These nurses suggested that their voices were silenced (often voluntarily) or were not expressed in terms of ethical decision making. Finally, they perceived that their approach to ethical decision making differed from physicians.